The Rome Treaty at 50: More honoured in the breach than in the observance? - Fredrik Erixon; Andreas Freytag; Gernot Pehnelt (European Centre for International Political Economy (ECIPE), 2007)
In March, 2007, the Treaty of Rome celebrates its 50th anniversary. The chief lesson from this remarkable period of European cooperation is the contribution to growth and prosperity from economic integration. The common commercial policy that emerged from this treaty has had a significant impact on European economic development. Equally important, regional liberalisation in Europe spurred multilateral trade liberalisation under the auspices of the GATT and the WTO . The Kennedy Round of trade liberalisation in the 1960s, facilitating considerable tariff reductions, was partly a response to European liberalisation. Similarly, the Uruguay Round of trade negotiations in 1986-1994 gained impetus form the Single Market programme. But regional liberalisation of trade in Europe has only been partial and confined to trade in goods. The service sector represents 75 percent of European production but only 20 percent of intra-European trade. European trade in services still suffers from considerable regulations. The agricultural sector is far less important for European wealth than services, but intra-European trade is severely distorted by the Common Agricultural Policy. To honour the theme of economic integration manifested in the Treaty of Rome, Europe must put the programme of trade liberalisation back on track. The liberalisation of trade in goods 50 years ago pushed global liberalisation. Considerable reduction of barriers to trade in services and agriculture is now necessary for Europe to not become an obstacle to international trade liberalisation.
Keywords: 330; Europäische Integration; Wirtschaftsintegration; Handelsliberalisierung; EU-Staaten